A Comparative Study of the Effect of Water Level on a Performance of a Hemispherical Acrylic Solar Distiller for Seawater Desalination - Bambang Raharjo; La Ode Mohammad Firman (Journal of Mechanical Engineering, Science, and Innovation, 2026)
Solar energy is considered one of the most promising renewable energy sources because it has the most reliable application potential in energy conservation. The main objective in this study is to compare the performance of two hemispherical solar still models, namely the Hemispherical Solar Still Black Paint (HSSBP) and the Hemispherical Solar Still Internal Reflective Mirror (HSSIRM). Enhancing solar distiller productivity and cost efficiency is profoundly influenced by its material design. Previous literature did not utilize more efficient materials in the solar distiller. The method of the current article utilizes relatively efficient materials for the cover of the solar distiller, which is made of acrylic with a thickness of 2 mm. The cylindrical seawater basin is made of iron with a diameter of 40 cm. This comprehensive study aims to increase the clean water production of the solar distiller by using an experimental setup use water levels different starting from 1cm, 2cm, and 3cm. The experimental results revealed that the seawater basin with a depth of 3 cm in section III achieved the highest cumulative productivity. Freshwater produced from model HSSBP in section III is 955 mL/m², compared to the productivity of 1 cm and 2 cm, which yielded 557 mL/m² and 875 mL/m². Then model HSSIRM can only produce 557 mL/m². The conclusion is productivity of the HSSBP model is better than that of the HSSIRM model.